2017
DOI: 10.1037/aca0000079
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of personality to differential conceptions of creativity: A systematic review.

Abstract: While neither the notion of personality being related to creativity, nor the idea that the diverse conceptions and measures of creativity can cloud the field are new, the 2 thoughts are rarely combined. Using a systematic review methodology, 1 overarching question was examined: Do differential creativity-personality relationships exist based on different creativity conceptions or measurement schemes? In the review, 188 reported relationships of creativity to personality across 96 peer-reviewed, empirical studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
109
3
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 178 publications
(129 citation statements)
references
References 35 publications
8
109
3
9
Order By: Relevance
“…Neuroticism was a more negative influence in this study (previously observed in Batey et al., ; Furnham & Bachtiar, ; Pretz & McCollum, ). Though conscientiousness did not show the opposite sign as in the earlier systematic review (Puryear, et al., ), neuroticism did. Neuroticism had the smallest overlap in the beta weight confidence intervals, suggesting it was the personality factor with the most differential influence on creativity when considering this grouping.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Neuroticism was a more negative influence in this study (previously observed in Batey et al., ; Furnham & Bachtiar, ; Pretz & McCollum, ). Though conscientiousness did not show the opposite sign as in the earlier systematic review (Puryear, et al., ), neuroticism did. Neuroticism had the smallest overlap in the beta weight confidence intervals, suggesting it was the personality factor with the most differential influence on creativity when considering this grouping.…”
Section: Discussioncontrasting
confidence: 55%
“…The overall findings of the present study align with those found in previous research (cf. Feist, ; Karwowski & Lebuda, ; Puryear, et al., ). For example, openness to experience was routinely the most salient predictor of creativity among the personality factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Ebeling-Witte, Frank, and Lester (2007) found that shyness is associated with neuroticism and (negatively related to) extraversion. Similarly, creativity has been found to have a positive relationship with openness and extraversion (Puryear, Kettler, & Rinn, 2016). Therefore, in an objective to examine the impact of shyness on creativity, it is meritous to explore the role of personality traits in the relationship.…”
Section: Discussionmentioning
confidence: 99%